Factors That Influence Enrolment and Retention in Ghana' National Health Insurance Scheme - Agnes Millicent Kotoh; Genevieve Cecelia Aryeetey; Sjaak Van der Geest (Kerman University of Medical Sciences, 2018)
Background The government of Ghana introduced the National Health Insurance Scheme (NHIS) in 2004 with the goal of achieving universal coverage within 5 years. Evidence, however, shows that expanding NHIS coverage and especially retaining members have remained a challenge. A multilevel perspective was employed as a conceptual framework and methodological tool to examine why enrolment and retention in the NHIS remains low. Methods A household survey was conducted after 20 months educational and promotional activities aimed at improving enrolment and retention rates in 15 communities in the Central and Eastern Regions (ERs) of Ghana. Observation, indepth interviews and informal conversations were used to collect qualitative data. Forty key informants (community members, health providers and district health insurance schemes' [DHISs] staff) purposely selected from two casestudy communities in the Central Region (CR) were interviewed. Several community members, health providers and DHISs' staff were also engaged in informal conversations in the other five communities in the region. Also, four staff of the Ministry of Health (MoH), Ghana Health Service (GHS) and National Health Insurance Authority (NHIA) were engaged in in-depth interviews. Descriptive statistics was used to analyse quantitative data. Qualitative data was analysed using thematic content analysis. Results The results show that factors that influence enrolment and retention in the NHIS are multi-dimensional and cut across all stakeholders. People enrolled and renewed their membership because of NHIS' benefits and health providers' positive behaviour. Barriers to enrolment and retention included: poverty, traditional risk-sharing arrangements influence people to enrol or renew their membership only when they need healthcare, dissatisfaction about health providers' behaviour and service delivery challenges. Conclusion Given the multi-dimensional nature of barriers to enrolment and retention, we suggest that the NHIA should engage DHISs, health providers and other stakeholders to develop and implement intervention activities to eliminate corruption, shortage of drugs in health facilities and enforce the compulsory enrolment stated in the NHIS policy to move the scheme towards universal coverage.